The Influence of Knowledge Generation on Organizational Creativity in CASNOS Foundation - Mesai Mohammed Salima; Ben Khalifa Ahmed; Hamza Baali; Mohammed El Amine Abdelli; Naima Bentouir; Afef Khalil (Journal of Information Technology Management)
This study aims to test the relationship between knowledge generation and organizational creativity. The second method was surveyed (analytical) using exploratory research through the survey as a data collection tool. The validity coefficient was measured as a reasonable degree of stability was obtained for a sample of (46) individuals. The data was analyzed using statistical package (SPSS V25). Descriptive Statistic Among the findings is that CASNOS has a medium level of the knowledge generation process, and there is a statistically significant effect of knowledge generation on the organizational innovation of CASNOS (El-Oued), according to the dimensions adopted in the study model.